ANALISIS PEMETAAN PROFIL BUDAYA ORGANISASI PADA PT BSI, TBK PASCA MERGER - Yoiz Shofwa Shafrani; Ida Puspita Wahyuningtyas; Siti Farida (Studia Economica : Jurnal Ekonomi Islam, 2022)
Islamic banking is a part of the Islamic finance industry which is currently becoming a concern in Indonesia. On February 1, 2021, a merger policy was issued for Sharia banks under BUMN, namely Bank Syariah Mandiri, BRI Syariah, and BNI Syariah. The merger of the three banks will certainly cause problems in the company's performance which reflects the performance of existing employees. There is a close relationship between the effectiveness of a company and organizational culture. A company needs a positive organizational culture model to be able to achieve its goals. Companies resulting from the merger are certainly vulnerable to changes in organizational culture. Especially considering that organizational culture is a variable that is very dynamic and always evolving and changes are difficult to predict. Organizational culture is then the process of mapping the profile of organizational culture at PT. BSI, Tbk is important so that it can be used as one of the guidelines for determining company strategy. The results of this study indicate that there are differences in the current type of culture which is considered hierarchical and what is expected is an adhocracy culture, so companies can focus more on considering external factors and always focus on new things that will spur innovation.Keywords : OCAI, Organization culture, BSI